Preservation of Tofu With Liquid Smoke From Coconut Shell - Ni Made Ayu Suardani Singapurwa; Anak Agung Made Semariyani; Ni Putu Chiana Adi Arandini (SEAS (Sustainable Environment Agricultural Science), 2022)
Tofu is one of the processed soybean products which is processed through the clumping of soy protein extract. Under normal conditions (room temperature) the average shelf life of tofu is 1-2 days. If it is more than this limit, the taste of tofu will become sour and rotten so it is not suitable for consumption. This study aims to determine the effect of coconut shell smoke and storage time on the chemical, microbiological, and organoleptic characteristics of tofu stored at room temperature. This study used a Completely Randomized Design (CRD) with two factors and two replications The first factor was concentrations (0%, 2%, 4%, 6%, and 8%) and the second factor was storage time (1, 2, 3 and 4 days). Observations were made objectively including total phenol, water content, ash content, fat content, and protein content. Microbiological analysis by testing Escherichia coli and Salmonella sp. While organoleptic parameters subjectively observed include color, aroma, texture, taste, and overall acceptance. The results showed that the concentration of 6% coconut shell liquid smoke in three days storage at room temperature resulted in the best tofu characteristics with a subjective assessment of neutral – to moderately like (score 4.40) and total phenol 0.57%, water content 82.34%, ash content 0.34%, fat content 5.72%, protein content 9.15%, Escherichia coli <3 APM/g, and negative for Salmonella sp. The shelf life of soaked tofu with a concentration of 6% coconut shell liquid smoke at room temperature is 3 days.